A Community Call to Action: Use of Quality Improvement Strategies to Address Youth Suicides. Issue 3 (3rd July 2021) - Esposito-Smythers, Christianne; Defayette, Annamarie B.; Whitmyre, Emma; Steinberg, Peter; Goldston, David B.; Asarnow, Joan Rosenbaum
ABSTRACT: Youth suicide clusters are a tragedy that no community should have to face. This paper details how a large community came together to better understand and prevent the future loss of young lives in their County using interdisciplinary quality improvement (QI) teams and a multi-component, continuous QI project. This includes the formation of a Youth Suicide Review Team, the development of a County wide Blueprint for youth and family behavioral health services, and the launching of a training consortium in evidence-based practice for behavioral health providers. The details surrounding these efforts are discussed, and the SAFETY-Acute/Family Intervention for Suicide Prevention is highlighted as an example of the training conducted. Finally, a discussion of some of the successes, barriers, and attempts to address obstacles along the QI pathway are offered. Broadly, this paper offers one model for how to leverage interdisciplinary academic-community partnerships to decrease risk for youth deaths by suicide by improving the quality of behavioral healthcare for youth and families.